THE IDEALIZATION OF FEMALE MODELS IN VICTORIA’S SECRET FASHION SHOW (IDEALISASI MODEL PEREMPUAN DALAM PERAGAAN BUSANA VICTORIA’S SECRET) - Muhammad Putra Wibowo; Lia Maulia Indrayani (Metalingua: Jurnal Penelitian Bahasa, 2021)
This paper aims to analyze and describe the message behind Victoria’s Secret Fashion Show, using semiotics theory by Roland Barthes. Based on the theory, the denotative meaning from Victoria’s Secret Fashion Show is that the show, in terms of function and purposes, is a mere fashion parade or clothing exhibition, while the connotative meaning of the show is that  Victoria’s Secret Fashion Show is a spectacle which conveys message that the brand practically idealizes the models. The idealization are seen from the way models are met with the requirements of body shape standards, how they are pictured as the models for other models in reaching successful career, and how they are supposed to present perfection to the spectators. This concept of idealization, in the perspective of semiotics, is a myth constructed by the show which lies within the culture of the global society.